Experimental study of single- and two-phase heat transfer of fractal-like structures - Mak, Joel Tse Hoi (Nanyang Technological University, 2020)
Flow boiling in microchannels has been shown to be a viable option for the use of thermal management. Fractal-like designs could be used to overcome the typical challenges faced by flow boiling in microchannels of high pressure drops and flow instabilities. This study experimentally investigated the viability of fractal-like designs for the use of thermal management. Four fractal-like designs (k = 1 to k = 4) were fabricated using Selective Laser Melting (SLM) with increasing branch levels. These channels were semi-circular, with a diameter ratio of 2−13, a length ratio of 0.5 and a bifurcation angle of 25˚. A multichannel parallel design consisting of four horizontal channels was used as a comparison. Flow boiling experiments were carried out at the three mass fluxes of 200, 400, and 600 kg/m2·s, with FC-72 as the coolant used. The thermal performances of the designs were evaluated based on the heat transfer coefficient and pressure drop. It was observed that the Parallel configuration had the lowest heat transfer coefficient curve compared to the fractal-like designs. It also had the largest pressure drop curve (i.e., the largest rate of increase of pressure) compared to the fractal-like designs. The increase in mass flux led to a higher peak heat transfer coefficient for all designs, but this increase was not proportionate for all mass fluxes. No correlation between having a more complex design and the heat transfer coefficient and pressure drop is noted. Different trends were noted at the different mass fluxes. Visualisation studies of the fractal-like designs display no signs of flow reversal and uniform flow split at the bifurcations. Entropy generation minimisation was also applied to the fractal-like model to obtain an optimal diameter ratio. This was unsuccessful due to the low contribution from pressure drop compared to the heat transfer.